Updates on the role of receptor activator of nuclear factor κB/receptor activator of nuclear factor κB ligand/osteoprotegerin pathway in breast cancer risk and treatment. Issue 1 (February 2017) - Bayer, Christian M.; Beckmann, Matthias W.; Fasching, Peter A.
Abstract : Purpose of review: Treatment with bisphosphonates and denosumab is the standard of care in bone metastatic disease. In addition, the adjuvant therapy of denosumab or bisphosphonates is very effective to prevent loss of bone mineral density, for example in osteoporosis. However, it is still unclear if this therapy has an influence on preventing cancer. Recent findings: Since the identification of novel genes in the 1980s, it took about 30 years until denosumab, as a fully human mAb against receptor activator of nuclear factor (NF)-κB ligand (RANKL), could be introduced to clinical practice. The discovery of the receptor activator of NF-κB/RANKL/osteoprotegerin pathway in the 1990s is an example of how modern databases of genes were utilized to discover new pathways relevant to a variety of diseases. The essential role of this pathway for the function, differentiation and survival of osteoclasts, and the influence on the bone microenvironment helped to understand the vicious circle of bone resorption and destruction in many skeletal diseases. Summary: In the following review, we discuss the important role of rational targeting concerning receptor activator of NF-κB/RANKL/osteoprotegerin and the bisphosphonate therapy and provide an update for the related treatment of patients suffering from breast cancer and further implications for clinical practice and research using denosumab as a potential chemoprevention in BRCA1-related breast cancer.